Regulation of endothelial cell functions by basement membrane-and arachidonic acid-derived products - Pozzi, Ambra (2009)
Angiogenesis, the formation of new blood vessels from preexisting vasculature, is required for normal physiological as well as pathological events. The angiogenic process requires endothelial cells to proliferate, migrate, and undergo tubulogenesis. These multistep processes necessitate secretion of pro-angiogenic growth factors, activation of specific intracellular signaling, and interaction of endothelial cells with basement membrane (BM) extracellular matrix components. The generation and release of angiogenic molecules are highly regulated and are influenced by numerous factors, including BM-derived fragments, proteolytic enzymes, as well as metabolites of arachidonic acid (AA). The interactions between these key modulators of angiogenesis is extremely complex, as AA metabolites can regulate the synthesis of soluble angiogenic factors, BM components, as well as enzymes capable of cleaving BM components, which result in the generation of pro- and/or anti-angiogenic products. Furthermore, some BM-derived fragments can alter the expression of AA-converting enzymes and consequently the synthesis of angiogenic factors. In this review we describe the relationship between BM components and AA metabolites with respect to the regulation of endothelial cell functions in health and disease.